2019
DOI: 10.1002/uog.20135
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of rectovaginal endometriosis using three‐dimensional gel‐infusion sonovaginography

Abstract: Deep infiltrating endometriosis (DIE) is characterized by the presence of foci of ectopic endometrial tissue, fibrosis and muscular hyperplasia that have penetrated more than 5 mm into the affected pelvic organs. Rectovaginal endometriosis is considered the most severe form of DIE, defined as infiltration by endometriotic lesions of both the rectum and the posterior vaginal fornix with possible extension to the rectovaginal septum 1 .The gold standard method for diagnosis of DIE is laparoscopy with biopsy 2 . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“… 22 It has recently been reported that 3D reconstruction of the coronal plane may allow for better visualization of pelvic structures, such as the posterior vaginal fornix and rectovaginal septum. 36 According to our experience, 37 3D modality should be complementary to 2D scan and be done dynamically during ultrasonographic examination. However, we deem that the main advantages of using 3D reconstructions are the estimation of the volume of DE nodules by VOCAL technique and the contribution in evaluating the degree of the stenosis of the bowel lumen in patients with rectosigmoid nodules at RWC‐TVS (Figure 1 and Figure S2 ); obviously, this was not possible by SVG, which is not based on the distention of the bowel lumen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 It has recently been reported that 3D reconstruction of the coronal plane may allow for better visualization of pelvic structures, such as the posterior vaginal fornix and rectovaginal septum. 36 According to our experience, 37 3D modality should be complementary to 2D scan and be done dynamically during ultrasonographic examination. However, we deem that the main advantages of using 3D reconstructions are the estimation of the volume of DE nodules by VOCAL technique and the contribution in evaluating the degree of the stenosis of the bowel lumen in patients with rectosigmoid nodules at RWC‐TVS (Figure 1 and Figure S2 ); obviously, this was not possible by SVG, which is not based on the distention of the bowel lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 3D acquisitions, being assessed off‐line by a dedicated post‐processing software, can be manipulated, rotated or scrolled through, in fascinating virtual navigation 22 . It has recently been reported that 3D reconstruction of the coronal plane may allow for better visualization of pelvic structures, such as the posterior vaginal fornix and rectovaginal septum 36 . According to our experience, 37 3D modality should be complementary to 2D scan and be done dynamically during ultrasonographic examination.…”
Section: Discussionmentioning
confidence: 99%
“…Without necessarily saying so, this obviously demonstrates there is an understanding that fluid in the POD is valuable for evaluating the posterior compartment and mapping disease with US. Moreover, sonovaginography, a technique that uses gel in the vagina to create a standoff view of the posterior compartment, including the RVS, has been studied and adapted with 3D technology . However, the sensitivity and positive predictive value of US for RVS disease could be improved .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sonovaginography, a technique that uses gel in the vagina to create a standoff view of the posterior compartment, including the RVS, has been studied 16 and adapted with 3D technology. 17 However, the sensitivity and positive predictive value of US for RVS disease could be improved. 3 In this era of a standardized approach to US performance and interpretation for endometriosis, SPG may be useful to advance our ability to map and measure disease in difficult-to-visualize anatomic areas.…”
Section: Discussionmentioning
confidence: 99%
“…The data available in literature is limited, with only a few reports from Brazil, Italy, Romania, and Australia, but the methods seems beneficial in the diagnosis of posterior deep infiltrating endometriosis. Up to date, no studies have reported its use in postmenopausal patients [22,[31][32][33].…”
Section: Imagingmentioning
confidence: 99%